International student mobility in a peripheral destination: The case of Mongolia - Li, Kun; Dembereldorj, Zoljargal (Journal of International Students, 2026)
The limited presence of international students in Mongolia raises concerns about the country’s role in global higher education. Guided by an expanded push–pull framework, this study examines the factors influencing international students’ choice to pursue tertiary education in Mongolia. On the basis of semistructured interviews with 25 international students, the key push factors identified include limited academic opportunities, economic hardship, social pressure, political instability, restrictive policies, and personal motivations. Mongolia’s attractiveness stems from affordability, accessible admissions, niche programs, and geographic, cultural, and ethnic proximity. The study also highlights facilitating factors—such as family support, social networks, and peer influence—and identifies reverse push–pull dynamics, including infrastructural deficiencies and experiences of social isolation. Recommendations include targeted marketing, enhanced promotion, strengthening niche academic programs, improving international student services, and implementing academic and social integration policies for local and international students. The findings offer insights for stakeholders in Mongolia and other peripheral destinations.